1890 Md. Laws 297 - (:unkn) unknown (My University, 1890)
Sabbath Breaking, ch. 290, § 1: No person whatsoever shall hunt with dog or gun on the Lord's day, commonly called "Sunday," nor shall profane the Lord's day by gunning, hunting, fowling, or by shooting or exploding any gun, pistol or firearm of any kind, or by any other unlawful recreation or pastime, and any person violating the provisions of this section shall, for every such offense, upon conviction before any justice of the peace for the county, forfeit the gun, pistol or other firearm used in such violation, and be fined not less than five dollars, nor more than thirty dollars. . .
Keywords: HUNTING REGULATION